Relocating world Christianity : interdisciplinary studies in universal and local expressions of the Christian faith - Cabrita, Joel, 1980- (Theology and Mission in World Christianity, 2017)
Existing scholarship on World Christianities tends to privilege the local and the regional. In addition to offering an explanation for this tendency, the editors and contributors of this volume also offer a new perspective. An Introduction, Afterword and case-studies argue for the importance of transregional connections in the study of Christianity worldwide. Returning to an older post-war conception of 'World Christianity' as an international, ecumenical fellowship, the present volume aims to highlight the universalist, globalising aspirations of many Christians worldwide. While we do not neglect the importance of the local, our aim is to give due weight to the significant transregional networks and exchanges that have constituted Christian communities, both historically and in the present day. Contributors are: J. Kwabena Asamoah-Gyadu, Naures Atto, Joel Cabrita, Pedro Feitoza, David C. Kirkpatrick, Chandra Mallampalli, David Maxwell, Dorottya Nagy, Peter C. Phan, Andrew Preston, Joel Robbins, Chloe Starr, Charlotte Walker-Said, Emma Wild-Wood.